Understanding success: An initial investigation considering the alignment of University branding with the expectations of future students - Helen O'Sullivan; Martyn Polkinghome; Mike O'Sullivan (Administrative Sciences, 2024)
This research investigates how university students define and perceive success, an area that is increasingly important to ensuring that a university's brand remains aligned to the expectations of future students. Over the next decade, university students will comprise members of Generation Z (Gen Z), and by recognizing this group of students' preferences and aspirations, universities can tailor their branding, educational portfolio, and overall campus experiences to ensure that together they resonate and satisfy evolving needs and demands. Using data based on a sample of Gen Z undergraduate students undertaking their degrees at three case study UK post-1992 universities, this research adopted an exploratory, interpretivist methodology. Data collected from semi-structured interviews were analyzed using recursive abstraction to identify underlying patterns and trends within the data. The research identified five key themes that Gen Z are using to define success, and these are the following: (1) being objective and task-driven; (2) embracing fluidity and subjectivity; (3) being ethically and morally responsible; (4) having resilience; and (5) accepting and learning from failure. Recommendations were made for actions that universities should start to take to enable them to work toward achieving this.
Keywords: 350; higher education; university; student; success; branding; Generation Z